Stability investigation of nonlinear vibrations of plates by R-functions method - Awrejcewicz, Jan; Kurpa, Lidiya; Mazur, Olga (Wydawnictwo Politechniki Łódzkiej, 2007)
The parametric vibrations of plates with cutouts subjected to in-plane periodic and compressive loads, are studied. The proposed approach is based on R-functions method and the classical variational approach. The influence of cutouts parameters, as well as static factors of load on stability regions and nonlinear vibrations are investigated.